The Challenges of Managing Depredation and Bycatch of Toothed Whales in Pelagic Longline Fisheries: Two U.S. Case Studies - Fader, Joseph E.; Elliott, Brianna W.; Read, Andrew J. (Frontiers in Marine Science, 2021)
Direct interactions with fisheries are broadly recognized as the leading conservation threat to small cetaceans. In open-ocean environments, one of the primary gear types implicated in these interactions is the pelagic longline. Unlike accidental entanglement in driftnets or deliberate entrapment by purse-seines, interactions between cetaceans and longlines are often driven by attraction of the animals to feed on bait or fish secured on the gear, a behavior known as depredation. Many small and medium-sized delphinid species have learned to exploit such opportunities, leading to economic costs to fisheries and a risk of mortality to the animals from either retaliation by fishermen or hooking or entanglement in fishing gear. Two pelagic longline fisheries in the United States experience depredation and bycatch by odontocete depredators: the Hawai‘i deep-set longline fishery, which is depredated primarily by false killer whales (Pseudorca crassidens), and the Atlantic pelagic longline fishery depredated primarily by short-finned pilot whales (Globicephala macrorhynchus). These fisheries are among the most intensively documented and managed pelagic longline fisheries in the world, with high levels of observer coverage, and bycatch mitigation measures required to reduce the mortality of seabirds, sea turtles and cetaceans. Both fisheries have active, multi-stakeholder ‘Take Reduction Teams’, enacted under the U.S. Marine Mammal Protection Act (MMPA), that are tasked to develop measures to reduce the bycatch of cetaceans below statutory reference points. Consequently, these two Teams represent model processes within which to address depredation and bycatch, having access to detailed, high-quality data on the nature and frequency of interactions with cetaceans, meaningful stakeholder involvement, resources to test potential solutions, and the institutional will to improve outcomes. We review how mitigation strategies have been considered, developed, and implemented by both Teams and provide a critical analysis of their effectiveness in addressing these problems. Notably, in the absence of straightforward avoidance or deterrence strategies, both Teams have developed gear and handling strategies that depend critically on comprehensive observer coverage. Lessons offered from these Teams, which have implemented consensus-driven management measures under a statutory framework, provide important insights to managers and scientists addressing other depredation problems.